Effect of post-mating GnRH treatmet on serum progesterone, luteinizing hormone levels, duration of estrous cycle and pregnancy rates in cows - Yildiz, H.; Kaygusuzo?lu, E.; Kaya, M.; Çenesiz, M. (My University, 2009)
Pregnancy rate, estrous cycle lenght, serum progesterone and luteinizing hormone (LH) concentrations were determined in gonadotropin releasing hormone (GnRH; 10.5 ?g synthetic gonadotrophin releasing hormone agonist, receptal) administered cows on day 12 post-mating (n=9) compared to control cows (n=8). Their oestrous cycles were synchronised by intramuscular administration of prostaglandin F2 alpha (its analog, cloprostenol) twice at 11 days interval. Estrous exhibited cows were mated naturally. Blood samples were collected every two days from all animals. Serum progesterone and LH concentrations were measured by ELISA method. GnRH administration significantly increased serum LH concentration which reached peak levels 2-3 h after treatment. However, serum progesterone concentration was not affected. There were no differences in mean progesterone concentrations on days 12 to 24 post-mating between GnRH administrated and control pregnant cows. However, in non pregnant animals, progesterone concentrations on days 16 in the treated group were lower than control group (P<0.01). Pregnancy diagnosis in animals made by B-mode ultrasonography between the 30th and 35th day showed that 77.7% of treated cows were pregnant compared to 50% in control group. Duration of the estrous cycle in the nonpregnant animals was not affected by the treatment (control, 21.3 ± 0.8 days; treated, 22.5 ± 0.5 days). In conclusion, this study supports the use of GnRH on day 12 post-mating as a method for enhancing pregnancy rates in lactating dairy cattle.
Keywords: Animalia; Bos